2001
DOI: 10.1016/s0005-2736(00)00373-4
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoperazine induces domain formation in zwitterionic phosphatidylcholine but not in charged phosphatidylglycerol bilayers

Abstract: The interaction of trifluoperazine with the zwitterionic lipids dipalmitoylphosphatidylcholine and dimyristoylphosphatidylcholine and with anionic dimyristoylphosphatidylglycerol was studied by means of microcalorimetry and fluorescence spectroscopy. Intercalation of drug molecules into the lipid bilayers was confirmed by the observed differential scanning calorimetry peak broadening and the decrease in chain-melting temperatures. For trifluoperazine:lipid mole ratios higher than 0.4 and 0.6 (for dipalmitoylph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…As we have shown some years ago phenothiazine derivative -trifluoperazine, can induce phase separation in phosphatidylcholine bilayers in temperatures below the main phase transition [11]. The fact that phenothiazines alter the properties of lipid bilayers may correlate with their ability to modulate the activity of multidrug-related transport proteins [12] and therefore they became the object of our studies.…”
Section: Accepted M Manuscriptmentioning
confidence: 94%
See 1 more Smart Citation
“…As we have shown some years ago phenothiazine derivative -trifluoperazine, can induce phase separation in phosphatidylcholine bilayers in temperatures below the main phase transition [11]. The fact that phenothiazines alter the properties of lipid bilayers may correlate with their ability to modulate the activity of multidrug-related transport proteins [12] and therefore they became the object of our studies.…”
Section: Accepted M Manuscriptmentioning
confidence: 94%
“…Recently the new parametergeneralized polarization slope (GPS) was also proposed for quantitative description of phase properties of lipid systems in which GP(λ ex ) dependence is linear [22]. Few years ago we used Laurdan generalized polarization to monitor the influence of TFP on the phase behavior of synthetic phosphatidylcholines: DPPC and DMPC [11]. In this work we observed that when bilayers were in the gel state the addition of trifluoperazine induced phase separation.…”
mentioning
confidence: 96%
“…Examples include anesthetics (7,8), cyclosporine (9), steroids (10), trifluoroperazine (11), and antibiotics like aminoglycosides (12) or macrolides (azithromycin) (13). This latter compound was also shown to markedly inhibit endocytosis (14,15), probably by interacting with lipids, modifying biophysical properties of membrane and affecting membrane dynamics in living cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that cis- (76) and trans-flupentixol (75) (see Fig. 5) inhibited the photoaffinity labeling of P-gp by substrate analogues [173].…”
Section: Phenothiazines and Related Compounds As Modulators Of Mdr Trmentioning
confidence: 99%
“…Besides CPZ (9), TFP (5) is another phenothiazine derivative whose interaction with membranes is relatively well known. In the extensive study of Hendrich et al [76], the influence of TFP (5) on model membranes formed from zwitterionic lipids (DMPC and DPPC) and negatively charged dimyristoylphosphatidylglycerol (DMPG) was investigated by means of DSC and fluorescence spectroscopy. For all lipids lowering of T m , calorimetric peak broadening, and ∆H decrease were recorded in the presence of the drug.…”
mentioning
confidence: 99%